Bacterial vaginosis and trichomoniasis: prevalence, associated factors, and performance of diagnostic tests - Cristina de Camargo, Kélvia; Alves, Rosane Ribeiro Figueiredo; Saddi, Vera Aparecida; Ramos, Jéssica Enocêncio Porto; Lima , Jamila Pimentel; Lemes de Souza, Camila; Baylão, Luciano Augusto; Santos, Silvia Helena Rabelo dos; Alves Ribeiro, Andrea (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Introduction: Bacterial vaginosis and vaginal trichomoniasis are frequent causes of health care demand. Objective: To estimate the prevalence, identify associated factors, and investigate the performance of diagnostic tests for bacterial vaginosis and trichomoniasis. Methods: Cross-sectional study with participants over 18 years old. All of them were submitted to an interview and gynecological examination with evaluation of vaginal secretion, pH verification, collection of material for Pap smear, wet mount test, Whiff test, bacterioscopy, and polymerase chain reaction for trichomoniasis detection. Logistic regression analysis was applied to identify associated factors with bacterial vaginosis. Diagnostic performance for bacterial vaginosis was evaluated following Amsel criteria, the Ison and Hay score, and the Pap smear, considering the Nugent score as the gold standard. As for trichomoniasis, diagnostic performance was evaluated through the Pap smear and the wet mount test, using the polymerase chain reaction as the gold standard. Results: The prevalence of bacterial vaginosis was 33.7%, and for trichomoniasis, 0.5%. The complaint of abnormal vaginal secretion was associated with the diagnosis of bacterial vaginosis (odds ratio 2.2). The diagnostic accuracy by Amsel criteria, the Ison and Hay score, and the Pap smear was 35.6, 97.0, and 84.2%, respectively. The sensitivity for trichomoniasis through wet mount test was 0.0%, and through the Pap smear, 100%. Conclusion: The prevalence of bacterial vaginosis was high, and trichomoniasis was low. The only associated factor with bacterial vaginosis was the report of abnormal vaginal secretion. The methods with the most accurate diagnostic performance for bacterial vaginosis were the Ison and Hay score and the Pap smear and, for trichomoniasis, the Pap smear.